Immune cell topography predicts response to PD-1 blockade in cutaneous T cell lymphoma - Darci Phillips (Nature Portfolio, 2021)
PD-1 blockade is effective for only a subset of patients with cutaneous T cell lymphomas. Here, the authors report a spatial biomarker that uses immune and cancer cell topography to predict response to PD-1 blockade in this disease.